Oriented Strand Board using Smaller Strand Size as a Core Layer - Yuziah M.Y, Nor; W.M, Nazri; K, Jamal; S, Rahim (International Journal of Engineering and Technology, 2018)
As a direct effect of its rapid growth, Leucaena leucocephala tree could be a leading raw material for bio-based composite panels. This fast growing tree and lesser used species in the wood industry can expand the choice of raw material for production of value added products. In this study, board properties of OSB using smaller strand size ofÂ  Leucaena leucocephala as core layer, physical and mechanical properties were found to be affected significantly by board density and resin content except for MOR in minor axis. However, strand size did not affect physical and mechanical properties except for MOR in major axis. Effects of board density on the mechanical properties were found to affect significantly different. The board density showed a significant effect on thickness swelling with a positive correlation. There is no significant difference on bending properties, internal bond strength and thickness swelling between combination of strand size of S1+S3 and S2+S3. Effect of resin content on bending properties showed significant difference of MOR in major axis and MOE values in both major and minor axis. Generally all treatment of OBS passed the general requirement of general purpose OSB even when the resin is as low as 5%.Â Â